The adventures of Baron Munchausen [videorecording (Blu-Ray)] - Schühly, Thomas, 1951-; McKeown, Charles; Gilliam, Terry; Neville, John, 1925-2011; Polley, Sarah; Idle, Eric; Williams, Robin, 1951-2014 (Criterion collection., 2023)
The boundless imagination of Terry Gilliam yields a dazzling fantasy of epic proportions. Inspired by the extravagant exploits of the fabled Baron Munchausen, this spectacle born of a famously turbulent production follows the whimsical eighteenth-century nobleman as he embarks on an outlandish quest that takes him from faraway lands to the moon to the belly of a sea monster and beyond, meanwhile waging battle against a vengeful sultan and the tyranny of logic.